Air pollution and health in Eastern India: Findings from a primary survey conducted in West Bengal and Jharkhand - Arup Halder; Aditi Kundu; Arunava Ghoshal (The Journal of Association of Chest Physicians)
Introduction: Exposure to air pollution has long been associated with mortality and shortened life expectancy and has been acknowledged as one of the growing risk factors that affect human health. Although air pollution is considered a global problem affecting rural and urban equally, it is still observed that the people of developing countries are disproportionately affected by it. Objectives of the Study: The present study aims to (1) understand the prevalence of upper respiratory symptoms, lower respiratory symptoms, and cardiometabolic and psychological health issues; (2) analyze the dichotomy in the degree of upper and lower respiratory symptoms based on the type of residence (rural/urban), age group, job profile (indoor/outdoor), and degree of pollution exposure; and (3) map the extent of reported health issues in the city of Kolkata. Methodology: A primary questionnaire survey was conducted in West Bengal and Jharkhand, where respondents were enquired about their health symptoms and their level of awareness of air pollution. An attempt was made to conduct a census survey in all of the target health camps, and only those who gave their consent were surveyed. Sample Description: The total sample (N) size was 2784 respondents (Jharkhand and West Bengal), with 1456 respondents from West Bengal and 1328 from Jharkhand. The total rural sample size was 417 respondents. The total urban sample size was 2367 respondents. Among the samples, 1369 were involved in indoor jobs (49%), 1415 were involved in outdoor jobs (51%), 2404 were exposed to both indoor and outdoor air, and 380 were exposed to only outdoor air pollution. Results and Discussion: More than 40% of the respondents reported sneezing, coughing, nasal congestion, or mood-related problems. More than 30% of the respondents reported sore throat or sleep-related problems, 14% had hypertension and 6% had diabetes. Among the various symptoms, cough was the predominant symptom in both rural and urban areas. Other than cough, all other symptoms suggestive of lower respiratory tract involvement were marginally higher in the urban areas in comparison to the rural areas. The urban population had higher numbers of symptoms per respondent than the rural counterparts. Lower respiratory symptoms (cough, chest discomfort, breathlessness) primarily increase with age and were the highest in the old age group (61 years and above). Lower respiratory symptoms were observed to be higher among outdoor workers, in comparison to indoor workers. Upper respiratory symptoms (sore throat, nasal congestion, and sneezing) except sinusitis were higher among outdoor workers in comparison to indoor workers. Except for cough and wheezing, most other lower respiratory symptoms (chest discomfort and tightening/degree of breathlessness) were observed to be higher among respondents who were exposed to both indoor and outdoor air pollution. Nasal congestion and sneezing were comparatively higher among people exposed to only outdoor air pollution. Sore throat and sinusitis were seen to be higher among respondents who were exposed to both indoor and outdoor air pollution. Population with both indoor and outdoor pollution exposure was more likely to have a higher number of symptoms per respondent than population with only outdoor pollution exposure. More than half of the respondents used liquified petroleum gas as their primary cooking fuel. At least 12% of the respondents use cooking fuel, which is attributed to the generation of unhealthy smoke. People of Kolkata also associated lifestyle diseases and psychological issues related to air pollution. Conclusion: Exposure to air pollution was associated with various upper and lower respiratory tract symptoms in more than half of exposed individuals. Symptoms suggestive of lower respiratory tract involvement were marginally higher in the urban areas in comparison to the rural areas. The urban population had higher numbers of symptoms per respondent than the rural counterparts. Symptoms suggestive of lower respiratory tract involvement increased with age and were highest after 61 years of age. Both upper and respiratory symptoms were more common in outdoor workers. Overall symptoms burden was more in Kolkata as compared to the overall study.